CARACAL: a versatile passive acoustic monitoring tool for wildlife research and conservation. Issue 1 (2nd January 2021) - Wijers, Matthew; Loveridge, Andrew; Macdonald, David W.; Markham, Andrew
ABSTRACT: Acoustic localisation technology has been widely tested and applied for passive acoustic monitoring and ecological research, however, hardware costs of commercially available devices limit scalability. Furthermore, few studies have explored its use with low-density arrays. We present a low-cost, custom-designed hardware and software system termed 'CARACAL' that is able to extract and localise weak acoustic signals. The key to this is the use of four microphones on each logger, allowing for phase-based measurements and the ability to enhance signal-to-noise ratio through beamforming. As a proof of concept, we test the functionality of the CARACAL system by conducting a gunshot localisation experiment and demonstrate animal call detection and localisation from a lion predation event. Results show the system could locate gunshots with an average accuracy of 33.2 ± 15.3 m within an array of 7 stations 500 m apart. When applied to animal call positioning, we show long range (> 1 km) localisation of three different species' calls, Cape buffalo, chacma baboon and spotted hyaena. With a cost of approximately £150 per unit, the CARACAL system provides a cost-effective solution for acoustic localisation over large areas. The system is open source and can be customised to suit a variety of wildlife research applications.